PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCABULAN DI KABUPATEN 50 KOTA - Putri, Melya Deana; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
As the law states, it is appropriate that the principles of a rule of law must be respected nd upheld, one of the principles is justice, which is the most central idea and at the same time the highest goal taught by every religion and humanity. The crime of sexual immorality is an immoral act committed against minors. In this case it is related to cases of sexual immorality in the District 50 Cities. The purpose of writing this thesis is first to know law enforcement against criminal acts of obscenity in the jurisdiction of District 50 Cities. Second, to determine the factors that hinder law enforcement of the crime of obscenity in the District 50 Cities. This type of research that wants to know the relationship between law and society, this research was conducted at the 50 City District Police, while the population and sample were all parties related to the problem studied, in this study the data source used was primary. data, secondary data, and tertiary data, data collection techniques in this study with interviews and literature study. From the results of the research problem, there are two main points that can be concluded. First, law enforcement against criminal acts of obscenity in the District 50 Cities is carried out by non-penal means, namely providing assistance to victims when taking legal channels, starting from reporting to the police so that their cases are processed, because the obstacles faced in this law enforcement are people who do not want to report, because they think it is all a disgrace to the family and if it is reported it will incur costs. Second, the inhibiting factor in law enforcement, namely internal and external factors. The author's suggestion, first, is expected to continue to make preventive efforts such as conducting socialization to remote areas. Both communities want to report to the authorities regarding the crime of sexual immorality.Keywords: Law Enforcement - Crime - Fornication